Estrategias metodológicas para el Aprendizaje de Factoreo en noveno de Educación General Básica, Unidad Educativa “San Felipe Neri”, 2022 - 2023. - Calderón Herrera, Edwin Andrés (2023)
The objective of this research project was to propose methodological strategies for the Learning of factoring in the ninth Year of Basic General Education of the Educational Unit "San Felipe Neri", because it has been observed that students present difficulties when developing factoring exercises, this originates due to the lack of methodologies and strategies that allow students to improve their attention and concentration, as well as interest in learning factoring. Methodologically, a qualitative approach was used, with a non-experimental design, of a descriptive type and purposeful level, the technique used was observation and as instruments bibliographic record cards, the same ones that were taken from academic bases such as scientific articles. , research project between so; For the selection of the articles, a study carried out within the past 10 years was taken as a reference, thus it was possible to reach the conclusion that there are several ICTs that support the teaching-learning process of factoring and a proposal was structured with the incorporation of some of them.